2022
DOI: 10.4062/biomolther.2021.145
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of the Active KRAS-Targeting Antibody inRas37 and a PI3K Inhibitor in Pancreatic Cancer

Abstract: KRAS activating mutations, which are present in more than 90% of pancreatic cancers, drive tumor dependency on the RAS/ mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)/AKT signaling pathways. Therefore, combined targeting of RAS/MAPK and PI3K/AKT signaling pathways may be required for optimal therapeutic effect in pancreatic cancer. However, the therapeutic efficacy of combined MAPK and PI3K/AKT signaling target inhibitors is unsatisfactory in pancreatic cancer treatment, because i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…E R K phosphorylation activates multiple substrates, which then regulate cell proliferation, apoptosis, metabolism, and immune response (17). The deregulation of the MEK/ERK pathway is common in cancer, such as ovarian cancer, melanoma, and PAAD (17,18). Besides, MEK/ERK inhibitors are proved to increase the radiosensitivity of cancer cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…E R K phosphorylation activates multiple substrates, which then regulate cell proliferation, apoptosis, metabolism, and immune response (17). The deregulation of the MEK/ERK pathway is common in cancer, such as ovarian cancer, melanoma, and PAAD (17,18). Besides, MEK/ERK inhibitors are proved to increase the radiosensitivity of cancer cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…In the peritoneal dissemination animal survival model, NVP-BEZ235 enhanced gemcitabine response (median survival in days was 16, 21, 28 and 30 in control, NVP-BEZ235, gemcitabine, and combination; P<0.05) (50). In PDAC subcutaneous xenografts, NVP-BEZ235 exhibited synergistic tumor growth inhibition in combination with pan-histone deacetylase inhibitor panobinostat (51) or inRas37 antibody (52). In vitro study using PANC-1 and MIA PaCa-2 PDAC cells revealed that NVP-BEZ235 markedly induced the ERK/MEK pathway.…”
Section: Preclinical Studies Targeting Kras Signaling In Pancreatic C...mentioning
confidence: 98%